2021
DOI: 10.1007/s11356-021-16737-7
|View full text |Cite
|
Sign up to set email alerts
|

Airborne concentrations of SARS-CoV-2 in indoor community environments in Italy

Abstract: COVID-19 pandemic raised a debate regarding the role of airborne transmission. Information regarding virus-laden aerosol concentrations is still scarce in community indoors and what are the risks for general public and the efficiency of restriction policies. This work investigates, for the first time in Italy, the presence of SARS-CoV-2 RNA in air samples collected in different community indoors (one train station, two food markets, one canteen, one shopping centre, one hair salon, and one pharmacy) in three I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
1
22
1
Order By: Relevance
“…These results may be attributed to the use of oxygen masks for patients, natural and mechanical ventilation in the studied wards, and environmental factor affecting bioaerosol concentrations. In a related study it has been reported that the absence of SARS-CoV-2 virus (present or not detected) in related hospital wards can be attributed to several reasons such as the strength of the source (number of infected patients), lack of an standard measurement protocol for airborne viruses, room volume, and the effect of mechanical and natural ventilation in the different places (ventilation rate) (Conte et al 2021). Grimalt et al (2022) also assessed the spread of SARS-CoV-2 in hospital areas and found that the highest risk of nosocomial infection might be occurred in the hospital areas that did not directly exposed to the exhaled breath of infected patients, thus the ventilation systems of the hospitals units should be evaluated to minimize the possible contagious influence via the direct monitoring of SARS-CoV-2 in the air.…”
Section: Resultsmentioning
confidence: 99%
“…These results may be attributed to the use of oxygen masks for patients, natural and mechanical ventilation in the studied wards, and environmental factor affecting bioaerosol concentrations. In a related study it has been reported that the absence of SARS-CoV-2 virus (present or not detected) in related hospital wards can be attributed to several reasons such as the strength of the source (number of infected patients), lack of an standard measurement protocol for airborne viruses, room volume, and the effect of mechanical and natural ventilation in the different places (ventilation rate) (Conte et al 2021). Grimalt et al (2022) also assessed the spread of SARS-CoV-2 in hospital areas and found that the highest risk of nosocomial infection might be occurred in the hospital areas that did not directly exposed to the exhaled breath of infected patients, thus the ventilation systems of the hospitals units should be evaluated to minimize the possible contagious influence via the direct monitoring of SARS-CoV-2 in the air.…”
Section: Resultsmentioning
confidence: 99%
“…The LoD in our study was 2.2 virus copies per liter of air, which is higher than some other SARS-CoV-2 air studies. 34,35 Many studies do not report LoD in terms of viral concentration in air, but the lowest reported values across several SARS-CoV-2 air sampling studies indicate large differences in LoD. 36 It is important to highlight that none of the samples-one fourmeter sample and parallel samples at one-and two-meter distancewere culture positive.…”
Section: Discussionmentioning
confidence: 99%
“…The LoD in our study was 2.2 virus copies per liter of air, which is higher than some other SARS‐CoV‐2 air studies. 34 , 35 Many studies do not report LoD in terms of viral concentration in air, but the lowest reported values across several SARS‐CoV‐2 air sampling studies indicate large differences in LoD. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Conte et al collected aerosol samples in different indoor community environments in Veneto, Emilia-Romagna, and Puglia, Italy. All of them tested negative for SARS-CoV-2 [50], suggesting that these measures are important for reducing the airborne transmission of SARS-CoV-2.…”
Section: The Spread Of Droplets Carrying Virus In the Indoor Environmentmentioning
confidence: 99%